Redução da atividade proteolítica da dentina após curtos períodos de aplicação de proantocianidina - Delgado, Cláudia Cristina; Scheffel, Débora Lopes Salles; Scheffel, Régis Henke; Pashley, David; Hebling, Josimeri (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
AbstractIntroductionCollagen cross-linkers have been investigated as inhibitors of the enzymatic activity of dentin, therefore improving the longevity of adhesive restorations.PurposeTo evaluate the effect of etched dentin treatment with proanthocyanidin (PA) in short periods of time on the inhibition of dentin metalloproteinases (MMP) activity in situ.Material and methodForty dentin specimens (1x1x6mm) were obtained from sound third molars and divided into 4 groups (n=10). The specimens were etched with 37% phosphoric acid for 15s and rinsed in deionized water. Then they were treated with the following solutions: water, 5% PA for 5s, 15s or 30s. The total MMP activity was analyzed by a colorimetric test (SensoLyte®). Absorbance data (412nm) were submitted to ANOVA and Tukey tests (α=0.05).ResultAll treatment periods were able to reduce the total activity of MMPs. The best results were observed for dentine treated with PA for 15s (63.1% reduction) and 30s (70.2%). Treatment for 5s was capable of inhibiting only 39.9% of the total MMP activity.ConclusionApplication of PA on the etched dentin in extremely short periods of time reduced the MMPs activity of dentin, even after 5s. However, the best results were obtained for the longer periods.

ResumoIntroduçãoAgentes promotores de ligações cruzadas têm sido investigados como inibidores da atividade enzimática da dentina, o que favoreceria a longevidade das restaurações adesivas.ObjetivoAvaliar o efeito do tratamento da dentina com proantocianidina (PA), em curtos períodos de tempo, na inibição da atividade de MMPs in situ.Material e métodoQuarenta espécimes de dentina (1×1×6 mm) foram obtidos de molares hígidos e divididos em quatro grupos (n=10). Os espécimes foram condicionados com ácido fosfórico por 15 s, seguido de lavagem em água deionizada. A dentina condicionada foi tratada com: água, 5% PA por 5 s, 15 s ou 30 s. A atividade de MMP foi analisada colorimetricamente (SensoLyte®) e os dados de absorbância (412 nm) foram submetidos aos testes de ANOVA e Tukey (α=0,05).ResultadoTodos os períodos de tratamento foram capazes de reduzir a atividade de MMPs, sendo que os melhores resultados foram observados para a dentina tratada com PA por 15 s (63,1% redução) e 30 s (70,2%). O tratamento por 5 s foi capaz de inibir 39,9% das MMPs.ConclusãoA aplicação de PA sobre a dentina condicionada foi capaz de reduzir a atividade de MMPs mesmo em períodos de tempo extremamente curtos, como 5 s. No entanto, melhores resultados foram obtidos com os maiores períodos de tratamento.
Reduction of the dentin proteolytic activity after short periods of application of proanthocyanidin
Keywords: Dentin; collagen; matrix-metalloproteinases; proanthocyanidin; Dentina; colágeno; metaloproteinase da matriz; proantocianidina